NEW TECHNOLOGY IN EDUCATION: THE 4K MODEL AND WAYS OF ITS IMPLEMENTATION - Lutfetdinova Rano Khusnetdinovna (Web of Journals Publishing, 2025)
The article analyzes the main approaches to organizing the modern educational process. The role of the 4K model, its features, and application issues are examined.
Keywords: 4K, collaboration, communication, creative thinking, critical thinking, analysis, evaluation, explanation, justification of one’s point of view, assumption, regulation, communication, cooperation, creativity, opinion corner, Mix-Freeze-Group, Frayer model, Stir-The-Class method.